Perancangan dan Pembuatan Sistem Informasi Administrasi pada Toko Asia Comm - Patrick Wijaya; Adi Wibowo; Leo Willyanto Santoso (Jurnal Infra, 2018)
Currently the recording of sales and purchases at this store is still done manually using paper. The existence of recording of data that is still done manually causes the accuracy of data is not guaranteed and difficulty in making reports. Based on the background of the problem, the authors designed an administrative information system that can overcome these problems.The process of making this program is equipped with PHP as programming language, bootstrap template as the display of this program, Mysql Phpmyadmin as database, notepad + + which is used to display programming source code and web browser as media to display result from website which have been made by notepad ++. The results obtained from applications that have been made, among others, the manufacture of sales and purchases that can be used to determine changes in stocks of goods and to calculate profit and loss, then orders, services, used sales and purchases used to calculate profit and loss and the list of goods and orders that must be met in accordance with the transactions that occurred.